2008
DOI: 10.1196/annals.1405.009
|View full text |Cite
|
Sign up to set email alerts
|

Classical Complement Pathway in Experimental Autoimmune Myasthenia Gravis Pathogenesis

Abstract: Mice deficient for complement factors C3, C4, or C5 are resistant to experimental autoimmune myasthenia gravis (EAMG). Acetylcholine receptor (AChR) immune lymph node cells (LNC) of C3 deficient mice produce less interleukin 6 (IL-6), and EAMG-resistant IL-6 deficient mice have less serum C3. Increased serum C1q-circulating immune complex (CIC) levels correlated with EAMG disease severity in RIIIS/J mice. The CIC promotes EAMG severity by stimulating the production of LNC IL-6, serum C1q, and C3 via FCgammaR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…We found that rats with M‐EAMG treated with rEV576 produced less IgG 1 , which in rat activates complement 33. The result is surprising given a lack of precedent for suppression of the C5 step of complement activation to influence humoral immunity; however, there is an emerging literature34 that demonstrates that alterations in complement or complement regulatory proteins may influence antibody profiles. The result suggests that complement activation, or perhaps rEV576 specifically, may have a direct effect on adaptive immunity.…”
Section: Discussionmentioning
confidence: 86%
“…We found that rats with M‐EAMG treated with rEV576 produced less IgG 1 , which in rat activates complement 33. The result is surprising given a lack of precedent for suppression of the C5 step of complement activation to influence humoral immunity; however, there is an emerging literature34 that demonstrates that alterations in complement or complement regulatory proteins may influence antibody profiles. The result suggests that complement activation, or perhaps rEV576 specifically, may have a direct effect on adaptive immunity.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, EAMG/MG can be treated by blocking activation of the classical complement pathway. Inhibitors of classical complement pathway factors can be used to treat MG and preserve activation of the alternate complement pathway 36. Thus, regulation of complement activation may be one possible therapeutic approach for AChRab‐positive GMG.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental autoimmune immune myasthenia gravis (EAMG) is a mouse model of myasthenia gravis, an autoimmune disease of unknown etiology characterized by the occurrence of auto-antibodies against the acetylcholine receptors (AChR) in the neuromuscular junctions (Christadoss et al, 2008;Conti-Fine et al, 2006). The symptoms of muscle weakness and paralysis are produced by complement-mediated destruction of AChR.…”
Section: Myasthenia Gravismentioning
confidence: 99%